Ocular complications in patients with Atopic Dermatitis – Review Article - Kosek, Szymon; Klonowska, Justyna; Walkowski, Radosław Jan; Wasiniewska, Weronika; Barański, Marcin; Kandefer, Tomasz; Sroka, Maria Izabela (Quality in Sport, 2025)
Atopic dermatitis is a chronic inflammatory disease that affects skin but is frequently associated with a variety of ophthalmological manifestations that can have a significant impact on patients quality of life. This review aims to gather current evidence on the pathophysiology, epidemiology, and clinical spectrum of ocular complications in AD, including eyelid dermatitis, blepharitis, conjunctivitis, keratoconus, cataract, retinal detachment, and dupilumab-associated ocular surface disease (DAOSD). Almost half of AD patients will experience ocular complications with main risk factors being disease duration and involvement of the periocular area. Diagnosis should primarily be based on thorough clinical evaluations and ophthalmological assessment. Management requires use of both topical and systemic drugs, patient education and in the most severe cases surgical intervention. Multidisciplinary cooperation most importantly between dermatologists and ophthalmologists is key for early diagnosis, effective treatment and prevention of complications associated with vision loss. Regular ocular screening is recommended for all patients with AD, especially those who are being treated with dupilumab.